PENDAPATAN USAHATANI KACANG PANJANG (Vigna sinensis L) DI KELURAHAN LANDASAN ULIN UTARA KECAMATAN LIANG ANGGANG KOTA BANJARBARU PROVINSI KALIMANTAN SELATAN - Wasdianta Wasdianta (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
To the effect this research is subject to be know technically cowpea farming management superior varietas PM 212 and to know costs, acceptance and cowpea farming income superior varietas PM 212. Methodic executed sampling by census which is take sample as a whole of total farmer population that labour cowpea farming which is as much 14 person.  Acquired production as big as 20.162,00 kg with production average as big as 1.440,14 kg / farmer Outgrows acquired acceptance it Rp.70.567.000's farmer,00 by average as big as Rp. 5. 040. 500,00 / farmer.  Averagely farmer earnings in one season plants out is as big as Rp. 3. 043. 138,78 / farmers